2011
DOI: 10.1521/aeap.2011.23.6.533
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of MI4MSM: How Useful is Motivational Interviewing as an HIV Risk Prevention Program for Men who have Sex with Men? A Systematic Review

Abstract: Among men who have sex with men (MSM), the principal risk practice for HIV infection is unprotected anal intercourse, often engaged in under the influence of alcohol and other substances. Both behaviors are targeted through the much-used counseling approach motivational interviewing (MI). We conducted a systematic review of the effectiveness of behavioral interventions adapting the principles and techniques of MI on HIV risk behaviors for MSM. Ten randomized controlled trials, which included 6,051 participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 47 publications
0
31
1
Order By: Relevance
“…Although all participants benefitted from having received their respective interventions (MI or education), those in the MI condition demonstrated significantly greater reductions in both substance use and UAI over the one year follow-up period. These findings are contrary to a recent review of MI-based interventions to prevent HIV risk for GBM (Berg et al, 2011). …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Although all participants benefitted from having received their respective interventions (MI or education), those in the MI condition demonstrated significantly greater reductions in both substance use and UAI over the one year follow-up period. These findings are contrary to a recent review of MI-based interventions to prevent HIV risk for GBM (Berg et al, 2011). …”
Section: Discussioncontrasting
confidence: 99%
“…Despite support for the efficacy of MI in reducing risk behavior in HIV-seropositive populations (Naar-King, Parsons, & Johnson, 2012), research is inconclusive regarding the effects of MI for HIV-negative GBM. Although Project Explore, a randomized controlled trial (RCT) testing the efficacy of MI over 10 sessions for HIV-negative GBM, found significant intervention effects on HIV incidence and UAI (Koblin, 2004), some recent reviews have questioned the efficacy of MI for reducing risky sex among GBM (Berg, Ross, & Tikkanen, 2011; Lundahl & Burke, 2009; Smedslund et al, 2011), while others have found that MI was more effective in reducing substance use than UAI among adult GBM (Berg et al, 2011; Morgenstern et al, 2009). Despite some evidence of MI reducing risky behaviors for certain sub-populations, further investigation is needed to determine its efficacy among HIV-negative substance-using YGBM.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 also shows the ongoing methodological problems associated with the existing evidence. These relate to issues such as conflicting and limited evidence: 43 on the one hand, the heterogeneity of populations included in studies and, on the other hand, where population criteria is more tightly specified, the small number of studies available for review. 48,62 Many of the studies available suffer from high or unclear risk of bias.…”
Section: Existing Evidence Synthesesmentioning
confidence: 99%
“…58 However, overall, these evidence syntheses do suggest cautious support for the efficacy of behavioural interventions among MSM. 34,43,49,55,56,58,59,62 Moreover, they suggest that evidence-based interventions have larger effects than non-evidence-based interventions. …”
Section: Existing Evidence Synthesesmentioning
confidence: 99%
“…Second, the two reviewers independently extracted data and determined quality assessment ratings for each article. Third, the two reviewers compared their extracted data and quality assessment ratings to assess inter-rater reliability as has been done in previously published systematic reviews (Berg, Ross, & Tikkanen, 2011; Lloyd & Operario, 2012). Next, a third or fourth reviewer provided input regarding the disagreement.…”
Section: Methodsmentioning
confidence: 99%